Effect of habitual music listening on attention, learning, and memory: An observational cross-sectional study among students in vijayawada. - Kachana, Srija; Yadavalli, Lakshmi Divya; Dampetla, Srujana; Maruthi, Wunnava; Devasena, Indla (Student's Journal of Health Research Africa, 2025)
Background Music has long been considered a tool for enhancing focus and cognitive performance, yet its effects on academic performance, particularly attention, learning, and memory, are still debated. This study explores the habituation of listening to music during study sessions among students in Vijayawada and evaluates its influence on academic engagement and cognitive function. Objective To determine the prevalence of listening to music while studying and assess its perceived impact on attention, learning, and memory. Methods An observational, cross-sectional, descriptive study was conducted among 142 undergraduate students aged 18–30 from various colleges around Siddhartha Medical College, Vijayawada. The sample included 58.5% females and 41.5% males. Data were collected through a structured questionnaire comprising multiple-choice questions regarding music preferences, reasons for listening to music, and its perceived effects on academic tasks. Descriptive statistics were used for analysis, and findings were presented in tables and charts. Results Most (92.3%) of students reported listening to music while studying, with 46.8% stating it improved concentration. Bollywood music was the most preferred genre (70%), and music was most often used during assignments (65%) and least favorite subjects (67.3%). About 79% felt that music helped relax their brain, and 39% reported extended study time with music. Moderate volume and speed were preferred by 63.6% of students. Conclusion Listening to music while studying is a prevalent practice among students, with most reporting positive effects on concentration, learning, and motivation. Music may be an effective cognitive aid, particularly during monotonous academic tasks. Recommendations Based on the findings, it is recommended that educational institutions consider integrating music as a potential tool for improving student focus and engagement during study sessions.